Ambient‐Temperature Energy Storage with Polyvalent Metal–Sulfur Chemistry. Issue 11 (13th October 2017) - Yu, Xingwen; Manthiram, Arumugam
Abstract: Electrochemical energy storage with ambient‐ or room‐temperature (RT) non‐aqueous sulfur chemistry has attracted much attention. In addition to the great attention to lithium–sulfur chemistry and sodium–sulfur chemistry, the attention toward polyvalent metal–sulfur chemistry has increased. RT sulfur batteries with magnesium, calcium, and aluminum anodes are of particular interest. In comparison to alkali metal (lithium and sodium) anodes, magnesium, calcium, and aluminum offer multiple advantageous features in terms of safety, abundance, and cost. Therefore, rechargeable battery systems with magnesium–sulfur (Mg–S), calcium–sulfur (Ca–S), and aluminum–sulfur (Al–S) chemistries are promising low‐cost options for large‐scale electrical energy storage. However, the research on these battery chemistries/technologies is still in its infancy and is currently hampered by many critical challenges. Here, the historical development, fundamental principles, recent progress, and key challenges of Mg–S, Ca–S, and Al–S batteries are summarized. Similarities and differences between the alkali metal (Li, Na, and K)–sulfur chemistries and the polyvalent metal (Mg, Ca, and Al)–sulfur chemistries are discussed. Finally, future research and development directions are suggested. Abstract : Research advances in electrochemical energy‐storage systems based on ambient‐temperature polyvalent metal–sulfur (Mg–S, Ca–S, and Al–S) chemistry are summarized. Fundamental principles, historical development, state‐of‐the‐art research, and critical challenges are discussed. Future research efforts and directions are also presented.